Rhabdomyolysis presenting with septic shock in a 21 year old female patient : a case report - Ersin Kuloglu (Journal of the Pakistan Medical Association)
Rhabdomyolysis is a clinical condition characterized by the release of intracellular content into the bloodstream, resulting in the breakdown of skeletal muscle. The released intracellular content includes electrolytes, enzymes, and myoglobin, leading to systemic complications. The clinical presentation may vary, ranging from an asymptomatic increase in serum levels of enzymes released from damaged muscles to worrisome conditions such as volume depletion, metabolic and electrolyte abnormalities, and acute kidney injury. The diagnosis is confirmed when the serum creatine kinase (CK) level is > 1000 U/L or at least 5x the upper limit of normal. In this study, we aimed to evaluate a 21-year-old female patient presenting with non-traumatic exercise-unrelated rhabdomyolysis, accompanied by acute renal failure and septic shock. Keywords: rhabdomyolysis, acute renal failure, sepsis, septic shock.